PELATIHAN PAR BERBASIS SMARTPHONE: PEMANFAATAN CANVA UNTUK MENINGKATKAN KETERAMPILAN DESAIN ANAK ASUH PANTI AL-IKHSANIYAH - Mulyani, Sri; Retnowati, Retnowati; Wahyudi, Eko Nur (Universitas Mataram, 2026)
The implementation of digital technology, particularly in graphic design, is crucial to enhancing students' skills in the digital era. However, many young people, especially those in orphanages, have not optimally utilized technology for learning and skill development. This is due to limited access and guidance in Information and Communication Technology (ICT). Therefore, this Community Service (PKM) activity aims to improve digital literacy among the children at Panti Asuhan Al-Ikhsaniyah through graphic design training using the Canva application on smartphones. The activity was conducted from August 1 to November 4, 2023, with 15 participants, consisting of 11 males and 4 females, all currently in junior high school. The method used in this activity was Participatory Action Research (PAR), which actively involved the stakeholders throughout each phase, including observation, theoretical and practical training, and reflection on the implementation of the material taught. The evaluation instruments used were pre-tests and post-tests, as well as rubrics for assessing design works. The results showed significant improvement, with 80% of participants successfully creating graphic design posters independently, producing 30 design works. Furthermore, 100% of participants were able to understand and use the Canva application. The average score on the design evaluation rubric increased to 16 out of 20, with 73% of participants feeling more confident in designing posters after the training. In conclusion, the application of digital technology in the form of graphic design using Canva significantly improved participants' skills and confidence, while also benefiting their digital skill development and creativity.